Physiological characteristics of endive, lettuce and chicory seeds as a function of spectral quality - Pretto, Matheus Milani; Fontana, Daniele Cristina; dos Santos, Jullie; Mariotto, Axel Bruno; Caron, Braulio Otomar; Schmidt, Denise (Comunicata Scientiae, 2020)
Seedling production is a critical step in the establishment of vegetables. This work aimed to evaluate the effect of different spectral qualities on the germination and vigor of endive, lettuce, and chicory seeds. The experiment was carried out in three stages. The first stage, two cultivars of lettuce (‘Crespa Repolhuda’ and ‘Vera’) and six spectral qualities (blue LED, red LED, blue + red LED, white LED, fluorescent and dark) were evaluated; the second stage, two cultivars of chicory (‘Lisa Escarola’ and ‘Palla Rosa’) and the same spectral qualities were evaluated. In the third stage, the spectral quality of the endive cultivar ‘Pão de Açúcar’ was evaluated. The experiments were performed in a completely randomized design, with four replications of 50 seeds each. The evaluated parameters were: germination percentage, first count, germination speed index, seedling length, and fresh and dry mass. Endive, lettuce and chicory seeds germinated both in the presence or not of light so that they can be classified as neutral photos. A spectral LED of red quality fostered the development of the most significant volume of fresh mass on the endive, lettuce, and chicory. All the spectral qualities stimulated root growth. The dark, on the other hand, promoted the most significant length of the aerial part, promoting seedlings etiolation.